Whirl Flutter Testing of ATTILA Tiltrotor Testbed : Initial Results - Hoff, S.C. van 't; Fonte, F.; Soal, K.; Schneider, O.; Kapteijn, K. (Vertical Flight Society, 2024)
This paper presents the preliminary results of the recent whirl flutter wind tunnel test campaign performed within the Advanced Testbed for TILtrotor Aeroelastics (ATTILA) project. The Froude-scale ATTILA testbed consists of a semi-span wing with powered tip-mounted proprotor reflecting the proprietary design of the Next Generation Civil TiltRotor (NGCTR). An overview of the ATTILA testbed, wind tunnel test procedures, team organisation and preliminary flutter results are presented. In line with pre-entry dynamic characterization tests, the wind-on test activities in the DNW Large Low-speed Facility (LLF) revealed notable force-dependent nonlinearity in the modal characteristics of, particularly, the wing torsion mode. Further dimensionality was added by early observations that damping in the rotor gimbal degree of freedom, attributed to stiction in the blade pitch mechanism, had the potential to substantially contribute to the damping of the fundamental wing-pylon modes. Nevertheless, the parallel exploitation of multiple monitoring and online modal estimation methodologies enabled a robust identification and safe test progression. The critical flutter mode was found to be configuration dependent, with the wing chord bending mode generally being marginally stable throughout most of the wind speed range, and the wing torsion mode displaying a sharp trend towards negative damping at higher speeds. Despite technical challenges, valuable test data was gathered to advance the experimental methods and support validation of the numerical tools used to obtained clearance for high-speed flight testing of the full-scale NGCTR Technology Demonstrator.